A Legal and Social Analysis of Women’s Protection in Ancient Israel - Frazier Nari; Handry Handry (SANCTUM DOMINE: JURNAL TEOLOGI, 2026)
The tradition of mohar (מֹהַר), or bride price in ancient Israel, played a significant role in shaping both the social structure and legal framework of marriage. While mohar is often seen as a payment made by the groom to the bride’s family, a closer examination reveals that it was more than just a financial transaction. It also served as a form of social security for women in a patriarchal society. This study explores the concept of mohar within the context of Torah law using a biblical and historical approach. This research employs a biblical analysis of Old Testament passages that mention mohar, including Genesis 34:12, Exodus 22:16-17, and 1 Samuel 18:25. Additionally, it compares the practice of mohar in ancient Israel with marriage laws in the broader Ancient Near Eastern context. The findings suggest that mohar was not merely a compensation to the bride’s family but also functioned as a safeguard for the bride within Israel’s social system. The Torah provides specific regulations concerning mohar, reflecting values of justice and responsibility in marriage. What makes this study unique is its in-depth exploration of the connection between mohar and Torah law, as well as its implications for understanding social justice in today's world.